Empowering Communities through Enhancing Environmental Awareness: A Case Study of Cikelat Village, Sukabumi, West Java in Community Service Activities - Aryo De Wibowo Muhammad Sidik; Edwinanto Edwinanto; Adi Padilah; Abdul Hak; Metodiusman Gulo; Gilang Insan Aghniya; Iqbal Tawakal; Mohammad Nashrul Hidayat; Fredy Yusman Alexius Lase; Muhammad Rifki Sofian; Gina Raodotul Jannah; Sinta Apriliani; Nadira Salsabila Oktaviani; Siti Latifah; Septiani Astuti; Ujang Faisal Kusnadi; Moh Ival Alpian S; Putri Erna Oktavia; Indri Aprianti; Siti Nur Annisa; Tiara Azzahra Anzani; Yurikeu Putri Agustin (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2024)
This article highlights a community service initiative titled